2015
DOI: 10.1088/0004-637x/804/1/34
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Galaxy Mergers and Luminous Active Galactic Nuclei

Abstract: It is not yet clear what triggers the activity of active galactic nuclei (AGNs), but galaxy merging has been suspected to be one of the main mechanisms fuelling the activity. Using deep optical images taken at various ground-based telescopes, we investigate the fraction of galaxy mergers in 39 luminous AGNs (M R -22.6 mag) at z ≤ 0.3 (a median redshift of 0.155), of which the host galaxies are generally considered as early-type galaxies. Through visual inspection of the images, we find that 17 of 39 AGN host g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 122 publications
(138 reference statements)
10
76
1
1
Order By: Relevance
“…Finally, Letawe et al (2004), through VLT optical spectroscopy, found that the host of this AGN is part of a group of at least five galaxies, and most probably underwent a collision with its nearest companion (∼4 arcsec). Later, Hong et al (2015) confirmed the merging state thanks to deep optical imaging. As a whole, this source could have undergone a restarted event triggered by the merger, but further observations are needed to confirm this scenario.…”
Section: Images From Surveys and The Literaturementioning
confidence: 77%
“…Finally, Letawe et al (2004), through VLT optical spectroscopy, found that the host of this AGN is part of a group of at least five galaxies, and most probably underwent a collision with its nearest companion (∼4 arcsec). Later, Hong et al (2015) confirmed the merging state thanks to deep optical imaging. As a whole, this source could have undergone a restarted event triggered by the merger, but further observations are needed to confirm this scenario.…”
Section: Images From Surveys and The Literaturementioning
confidence: 77%
“…(e.g., Letawe et al 2010;Liu et al 2012;Hong et al 2015), dust-reddened (Urrutia et al 2008;Kocevski et al 2015;Fan et al 2016 Schawinski et al 2011Schawinski et al , 2012Mechtley et al 2016;Villforth et al 2017) redshifts dismiss the importance of major mergers in driving nuclear activity.…”
Section: Are Mergers Important For Triggering Agns?mentioning
confidence: 99%
“…AGN are thus often found in morphologically dis-turbed galaxies or ULIRGs (e.g. Urrutia et al 2008;Bennert et al 2008;Yuan et al 2010;Koss et al 2011;Hong et al 2015).…”
Section: The Significance Of Major Merger Quenchingmentioning
confidence: 99%